2019
DOI: 10.3389/fnins.2019.00409
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Models of Traumatic Brain Injury and a Place for Drosophila in TBI Research

Abstract: Traumatic brain injury (TBI), caused by a sudden blow or jolt to the brain that disrupts normal function, is an emerging health epidemic with ∼2.5 million cases occurring annually in the United States that are severe enough to cause hospitalization or death. Most common causes of TBI include contact sports, vehicle crashes and domestic violence or war injuries. Injury to the central nervous system is one of the most consistent candidates for initiating the molecular and cellular cascades that result in Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 106 publications
(157 reference statements)
0
18
0
1
Order By: Relevance
“…We found that TBI in flies shares key characteristics with TBI in mammals, including temporary incapacitation, short-term ataxia, progressive neurodegeneration, intestinal barrier dysfunction, hyperglycemia, and shortened lifespan (Katzenberger et al 2013(Katzenberger et al , 2015a. Furthermore, consistent with findings of an activated Nuclear Factor kappa B (NF-B) response in mammals, transcriptional gene targets of the homologous NF-B-mediated Toll and Immune-deficiency (Imd) signaling pathways are rapidly and persistently activated following TBI in multiple fly models (Katzenberger et al 2013(Katzenberger et al , 2015a(Katzenberger et al , 2015b(Katzenberger et al , 2016Barekat et al 2016;Ratliff et al 2016;Sen et al 2017;Shah et al 2019). For example, expression of major Toll and Imd gene targets, antimicrobial peptides (AMPs), substantially increases within 30 min after TBI and remains elevated for at least 24 h (Katzenberger et al 2016).…”
Section: Introductionmentioning
confidence: 73%
“…We found that TBI in flies shares key characteristics with TBI in mammals, including temporary incapacitation, short-term ataxia, progressive neurodegeneration, intestinal barrier dysfunction, hyperglycemia, and shortened lifespan (Katzenberger et al 2013(Katzenberger et al , 2015a. Furthermore, consistent with findings of an activated Nuclear Factor kappa B (NF-B) response in mammals, transcriptional gene targets of the homologous NF-B-mediated Toll and Immune-deficiency (Imd) signaling pathways are rapidly and persistently activated following TBI in multiple fly models (Katzenberger et al 2013(Katzenberger et al , 2015a(Katzenberger et al , 2015b(Katzenberger et al , 2016Barekat et al 2016;Ratliff et al 2016;Sen et al 2017;Shah et al 2019). For example, expression of major Toll and Imd gene targets, antimicrobial peptides (AMPs), substantially increases within 30 min after TBI and remains elevated for at least 24 h (Katzenberger et al 2016).…”
Section: Introductionmentioning
confidence: 73%
“…In this study, we are using Drosophila melanogaster as a model to study TBI. The complex brain and nervous system of flies make it a very powerful model for neuroscience research (25,26). Consistent with mammalian and human TBI studies, flies subjected to rapid acceleration and impact exhibit TBI related secondary phase symptoms including innate immune response, neurodegeneration, disrupted sleep cycles and a decreased lifespan (27,28).…”
Section: Introductionmentioning
confidence: 87%
“…Behavioral effects like loss of motor skills, coordination, and balance impairment are commonly observed post-TBI in experimental models and also in clinical patients (25). Mild TBI in mice is shown to alter diurnal locomotor activity and response to light (78).…”
Section: Tbi Impairs Locomotor Activity and Climbing Ability In Drosomentioning
confidence: 99%
“…We and others have developed fly TBI models to investigate the pathways that control development of secondary injuries following TBI (Katzenberger et al 2013(Katzenberger et al , 2015a(Katzenberger et al , 2015bBarekat et al 2016;Sen et al 2017;Lee et al 2019;Putnam et al 2019;Sanuki et al 2019;Shah et al 2019;Saikumar et al 2020). Our model uses a spring-based instrument called a High-impact trauma (HIT) device to inflict physical trauma by rapid acceleration-deceleration forces (Katzenberger et al 2013(Katzenberger et al , 2015a(Katzenberger et al , 2015b(Katzenberger et al , 2015c(Katzenberger et al , 2016Fischer et al 2018;Swanson et al 2020).…”
Section: Introductionmentioning
confidence: 99%